Hubungan Antara Teaching Style (Gaya Mengajar Guru) Dengan Minat Belajar Matematika Pada Siswa SMK Muhammadiyah 4 Wonogiri - Primajasa, Ell Yuna; , Dra. Partini, M.Si (2016)
Mathematics has always been considered as one of the lessons were quite difficult and unpleasant for the student. Efforts to repair and improve the quality of mathematics teaching has been conducted, but complaints about the difficulties is often heard. Learning difficulties that arise are not sourced from the students, but also come from the outside, for example how the presentation of the lessons conducted by teachers who are not interesting so that students have a low interest in learning mathematics. The purpose of this study was to determine the relationship of teaching styles with student`s interest in learning mathematics at SMK Muhammadiyah 4 Wonogiri. The hypothesis of this study there is a relationship between teaching styles and students' interest in learning mathematics at SMK Muhammadiyah 4 Wonogiri. Subjects of this study was 50 students of SMK Muhammadiyah 4 Wonogiri. Sampling technique using an incidental cluster sampling. Collecting data in this study using two scales, the scale of teaching style and the scale of student`s interest in learning mathematics. Analysis of the data using the product moment correlation from Pearson. The results of the analysis of the data obtained correlation coefficient (r) is 0.576 with significance (p) 0,000 which means that there is a significant positive relationship between teaching style with student`s interest in learning mathematics. Effective contribution of variable teaching style with student`s interest in learning mathematics is 33.18%. This means that there are 66.82% of other variables that may affect the student`s interest in learning mathematics outside variable teaching style. Variable teaching style has the empirical mean (ME) 48.34 while the hypothetical mean (MH) 42.5 so its included in the high category. Variable student`s interest in learning mathematics has the empirical mean (ME) 72.68 while the hypothetical mean (MH) 62.5. The conclusion of this research that there is a significant positive relationship between teaching style with student's interest in learning mathematics at SMK Muhammadiyah 4 Wonogiri. This means that when teachers use a teaching style with the student centered approach, the student`s interest in learning mathematics will be higher. Conversely when teachers use a teaching style with teacher centered approach, the student`s interest in learning mathematics would be lower. Key : teaching style, student`s interest in learning mathemathics, student SMK